Pons-Sanz, Sara M., and Louise Sylvester, eds. 2023. Medieval English in a Multilingual Context: Current Methodologies and Approaches. Cham: Palgrave Macmillan. Pp. 549. ISBN 9783031309465. - Brady, Lindy (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
Book review of Pons-Sanz, Sara M., and Louise Sylvester, eds. 2023. Medieval English in a Multilingual Context: Current Methodologies and Approaches. Cham: Palgrave Macmillan. Pp. 549. ISBN 9783031309465.